2023
DOI: 10.1002/wfs2.1510
|View full text |Cite
|
Sign up to set email alerts
|

Role of postmortem toxicology in drowning investigations

Ilkka Ojanperä,
Pirkko Kriikku

Abstract: Drowning is the third most common cause of unintentional injury death worldwide. In forensic medicine, drowning refers to an event in which the victim dies due to liquid penetrating into the airways or due to submersion in a liquid. Medico‐legal examination of bodies found in water is a challenging task. Establishing proper cause and manner of death requires the joint efforts of the police, medical examiner, and representatives of postmortem toxicology. Information of the circumstances, the victim's individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The retrospective and epidemiological studies showed that the risk of unintentional drowning increased with alcohol use, and the rates of alcohol involvement were generally higher in river compared with coastal drowning and among males (e.g., [25,42]). However, many jurisdictions do not require toxicology reporting for drowning cases [49], and so the true extent of alcohol involvement may be underestimated. Finally, only a few studies looked specifically at interventions to reduce alcohol-related harm around water [30,47,48].…”
Section: Prevalence and Epidemiology Of Alcohol Use In Aquatic Enviro...mentioning
confidence: 99%
“…The retrospective and epidemiological studies showed that the risk of unintentional drowning increased with alcohol use, and the rates of alcohol involvement were generally higher in river compared with coastal drowning and among males (e.g., [25,42]). However, many jurisdictions do not require toxicology reporting for drowning cases [49], and so the true extent of alcohol involvement may be underestimated. Finally, only a few studies looked specifically at interventions to reduce alcohol-related harm around water [30,47,48].…”
Section: Prevalence and Epidemiology Of Alcohol Use In Aquatic Enviro...mentioning
confidence: 99%